KAJIAN MAKNA HIDUP TERHADAP PANDANGAN PARAMEDIS DAN TOKOH AGAMA TENTANG PASIEN KANKER DARI PERSPEKTIF LOGOTERAPI FRANKL - Irianto Putra Lengkey; Jacob Daan Engel (Institut Agama Kristen Negeri Manado, 2022)
This study aims to examine the meaning of life from the views of paramedics and religious leaders about cancer patients at Ken Saras Hospital, Ungaran. This research is motivated by the fact that most cancer patients lose the meaning of their life. This study applies a descriptive qualitative research approach. Interviews and observations were used to collect data. This research shows that cancer patients need support and assistance to be able to rediscover the meaning of their lives. They can get this support and assistance from various parties, namely families, paramedics and religious leaders. This paper is expected to help families, paramedics and religious leaders to be able to provide support and assistance to cancer patients so that they can rediscover the meaning of their lives. For this purpose, the authors focus on Ken Saras Hospital which treats cancer patients. The author hopes that the results of this study can be a reference for families, paramedics and religious leaders to provide support and assistance to cancer patients in order to find the meaning of their lives.